2011
DOI: 10.1186/1476-511x-10-127
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil intake is inversely related to cancer prevalence: a systematic review and a meta-analysis of 13800 patients and 23340 controls in 19 observational studies

Abstract: Dietary fat, both in terms of quantity and quality, has been implicated to cancer development, either positively or negatively. The aim of this work was to evaluate whether olive oil or monounsaturated fat intake was associated with the development of cancer. A systematic search of relevant studies, published in English, between 1990 and March 1, 2011, was performed through a computer-assisted literature tool (i.e., Pubmed). In total 38 studies were initially allocated; of them 19 case-control studies were fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(198 citation statements)
references
References 76 publications
(82 reference statements)
5
181
3
2
Order By: Relevance
“…This product represents the primary source of lipids in the Mediterranean diet, which has been linked to positive health benefits. Indeed, this diet reduces the risk from a number of diseases, mainly those containing an inflammatory component such as cardiovascular diseases, certain types of cancer, diabetes, metabolic syndrome, arthritis and Alzheimer's disease [1][2][3][4][5][6]. Thus, increased VOO consumption, one of the main distinguishing features of the Mediterranean diet, is likely to have a positive impact on the general population's health and consequently, on the budgets allocated to healthcare systems.…”
Section: Introductionmentioning
confidence: 95%
“…This product represents the primary source of lipids in the Mediterranean diet, which has been linked to positive health benefits. Indeed, this diet reduces the risk from a number of diseases, mainly those containing an inflammatory component such as cardiovascular diseases, certain types of cancer, diabetes, metabolic syndrome, arthritis and Alzheimer's disease [1][2][3][4][5][6]. Thus, increased VOO consumption, one of the main distinguishing features of the Mediterranean diet, is likely to have a positive impact on the general population's health and consequently, on the budgets allocated to healthcare systems.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have shown that a high OMR in tissues or cholesteryl-esters is associated with several diseases including cancers such as prostate, bowel and breast cancer, CVD, autoimmune diseases and inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease (Godley et al 1996;Harvei et al 1997;Gogos et al 1998;Simonsen et al 1998;Yang et al 1999c;Simopoulos 2008;Murff et al 2011). Intake of many types of fat have been examined, with a suggestion of a threshold of n-6 PUFA, and reduced rates of disease for fats or oils low in n-6 PUFA, including animal fat (Zock and Katan 1998;Freedman et al 2008;Alexander et al 2010;Brennan et al 2010;Dong et al 2011;Gilsing et al 2011;Liu et al 2011;Psaltopoulou et al 2011;Chajes et al 2012). Moreover, supplementation with longchain n-3 FA fails where there are high rates of consumption of n-6 PUFA.…”
Section: Components Of Animal Fat With Known Health Benefitsmentioning
confidence: 99%
“…Several studies have reported an inverse relationship between olive oil or other monounsaturated fats consumption and breast cancer (Wolk et al, 1998;Thiebaut et al, 2007;Psaltopoulou et al, 2011;Tsuji et al, 2012). There are also several studies which report either no or weak association between monounsaturated fat and breast cancer (Sieri et al, 2008;Zhang et al, 2011).…”
Section: Monounsaturated Fats and Olive Oilmentioning
confidence: 99%